Analisis Nilai Ekonomi Agrowisata Taman Edelweis di Desa Besakih, Kecamatan Rendang, Kabupaten Karangasem - WIJAYAKUSUMA, PUTU AGUS YUDI; DARMAWAN, DWI PUTRA; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p49, 2023)
Economic Analysis of Edelweis Park Agrotourism, in Besakih Village, Rendang Distric, Karangasem Regency Edelweis Park Agrotourism with Kasna flowers as a characteristic, was developed for the first time in Karangasem Regency and there has never been a study of the economic value, seen from the visits made by tourists, to estimate how much economic value is given by tourists. Research was conducted with the aim to determine the factors that affect the frequency of tourist visits and the economic value of Edelweis Park Agrotourism. The research location was determined purposively and determination of the sample using the accidental sampling method. Analysis of the factors that affect the frequency of tourist visit using multiple linear regression while the analysis of the economic value of using the cost method of travel that look a gain suplus consumers. The results showed that the factors that affect the frequency of visits to Edelweis Park Agrotourism are end of education and travel costs. The calculation of consumer surplus with the average number of tourist visits from 2018 to 2020, the economic value of Edelweis Park Agrotourism obtained is Rp. 20,034,738,305.00. Based on the results, expected that the manager to add and improvement facilities and able to join with travel agency to provide affordable travel packages for visitors.